Antagonism of P2Y12 or GPIIb/IIIa receptors reduces platelet-mediated myocardial injury after ischaemia and reperfusion in isolated rat hearts - Barrabés, José A; Inserte, Javier; Mirabet, Maribel; Quiroga, Adoración; Hernando, Victor; Figueras, Jaume; Garcia-Dorado, David (Thrombosis and haemostasis, 2010)
Platelets activated during experimental acute myocardial infarction (AMI) contribute to myocardial injury. This study aimed to investigate whether platelets from patients with AMI increase myocardial injury after ischaemia and reperfusion in isolated rat hearts and the modification of this effect by the P2Y12 receptor antagonist cangrelor and the glycoprotein IIb/IIIa receptor blocker abciximab. Isolated rat hearts were subjected to 40 minutes of global ischaemia and 60 minutes of reperfusion. Hearts (four simultaneous experiments per patient) were infused with platelets from nine AMI patients (seven thrombolysed, all on aspirin), untreated or incubated with 10 microM cangrelor or 5 microg/ml abciximab. Control experiments were performed using platelets from healthy volunteers and platelet-poor plasma. P-selectin expression on isolated platelets was higher in AMI patients than in controls and was not modified by the treatments. Control platelets or platelet-poor plasma did mild or no harm. In contrast, platelets from AMI patients significantly augmented myocardial injury, as demonstrated by worse left ventricular (LV) developed pressure, higher maximal LV end-diastolic pressure and coronary resistance, and greater lactate dehydrogenase release and infarct size. Both cangrelor and abciximab greatly attenuated these effects. In conclusion, activated platelets from AMI patients increase myocardial injury after ischaemia and reperfusion, and cangrelor and abciximab attenuate this effect. The results support the notion that very early antiplatelet treatment might reduce infarct size by direct effects on reperfused myocardium in these patients.